Functional fiber mesh material based on carbon fiber melt direct writing to absorb antibiotics in water and preparation method thereof

By using melt direct writing technology on carbon fibers, the problems of low antibiotic removal efficiency and difficulty in recycling adsorbents in the prior art are solved, and the effects of efficient adsorption and stable recovery are achieved.

CN116078356BActive Publication Date: 2025-02-11SHANGHAI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211280697.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2025-02-11
Estimated Expiration
2042-10-19

AI Technical Summary

Technical Problem

The prior art has problems of low efficiency and difficulty in recycling adsorbents in removing antibiotics in natural water environments. Traditional functional nanomaterials are not suitable for water treatment and have a risk of environmental pollution.

Method used

Using carbon fiber-based melt-direct writing technology, functional fiber mesh material was prepared. By physically blending iron tetroxide, activated carbon and polymer powder, heated and melted at high temperature, the molten mixture was sprayed on the air pressure. On carbon fibers, a mesh structure is formed to improve adsorption efficiency.

Benefits of technology

It realizes efficient adsorption of antibiotics in water bodies, provides strong specific surface area and porosity, and the mechanical properties and stability of fiber materials make them stable and easy to recover in water bodies, significantly improving the antibiotic removal rate and material reuse performance. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116078356B_ABST
    Figure CN116078356B_ABST
Patent Text Reader

Abstract

The present invention discloses a functional fiber mesh material and a preparation method based on carbon fiber melt direct writing to absorb antibiotics in water, belonging to the field of water body remediation technology. Ferroferric oxide, activated carbon and polymer powder are physically blended as direct writing raw materials, shaken and added to a feed barrel; the blend in the feed barrel is heated and melted into a molten state at a high temperature, and the air pressure generated by the air pump is used as a power source to extrude the molten mixture from the spinning nozzle; the carbon fiber is placed on a collection plate, and a micro-nano mesh fiber material is prepared on the carbon fiber using melt direct writing technology. The present invention is based on the preparation of micro-nano mesh composite materials by carbon fiber with the aid of melt direct writing technology, which has excellent mechanical properties, acid and alkali corrosion resistance, and is easy to recycle. The micro-nano mesh structure prepared on the surface of the carbon fiber has a strong specific surface area to provide a larger adsorption capacity, and provides more active sites for contacting antibiotics, thereby adsorbing and removing antibiotics in sewage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water body restoration, and in particular to a functional fiber mesh material based on carbon fiber melt direct writing to absorb antibiotics in water and a preparation method thereof. Background Art

[0002] With the development of modern analytical technology and the enhancement of people's environmental safety awareness, the emergence of emerging organic pollutants such as antibiotics in natural water environments has attracted widespread attention. Antibiotics are widely used and used in large quantities, resulting in a high probability of their occurrence in natural water environments. Many domestic and foreign research reports have pointed out that a variety of antibiotics have been detected in natural water environments, including natural water bodies such as oceans, rivers, lakes and groundwater. Since most antibiotics have poor biodegradability, the biological wastewater treatment process currently used by most sewage treatment plants cannot effectively remove antibiotics in sewage, so a certain amount of antibiotics still remain in the effluent. Although the concentration of antibiotics in natural water environments is relatively low, their potential harm to ecosystems and human health cannot be ignored. As antibiotics are frequently detected in natural water environments, more and more studies are being conducted on their hazards. According to existing literature reports, the hazards of antibiotics in natural water environments can be attributed to three aspects, namely biological toxicity, induction of drug-resistant bacteria or drug-resistant genes, and threats to drinking water safety.

[0003] Adsorption has become the preferred method for water pollution remediation due to its advantages of high efficiency, green, simple process and low cost. This method generally uses porous solids to adsorb pollutants in wastewater to purify the wastewater. The significant advantage of this method is that no more toxic or more difficult to degrade pollutants are produced in the process of removing pollutants. Studies have shown that after intermittent and continuous adsorption of several antibiotic wastewaters such as sulfonamides, trimethoprim and tetracycline using activated carbon or other solid functional nanomaterials, the removal rate of antibiotics in wastewater is between 50% and 95%. Although this method can efficiently treat antibiotic wastewater, some traditional functional nanomaterials currently used are not suitable for water treatment scenarios, and the adsorbed solids have become a new environmental pollutant due to their existence form and the disadvantages of being difficult to recover. The limitation of their specific surface area has also caused a bottleneck for the removal effect of antibiotics. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a functional fiber mesh material based on carbon fiber melt direct writing to absorb antibiotics in water and a preparation method thereof. With the help of melt direct writing technology, micro-nano functional fibers are directly written on carbon fiber to construct a mesh structure to provide a strong specific surface area and porosity, thereby achieving high adsorption efficiency; the excellent mechanical properties and stable physicochemical properties of carbon fiber enable the functional adsorption material to be stably used in water and conveniently recycled; the catalyst is fixed on the carbon fiber carrier matrix to reduce the shear stress on the catalyst particles, thereby achieving efficient removal of antibiotics in water.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a functional fiber mesh material based on carbon fiber melt direct writing to absorb antibiotics in water, comprising the following steps:

[0007] S1. Physically blend ferroferric oxide, activated carbon and polymer powder as direct writing raw materials, shake well and add them into the feed barrel;

[0008] S2, heating the blend in the feed barrel at high temperature to melt it into a molten state, and using the air pressure generated by the air pump as a power source to extrude the molten mixture from the spinning nozzle;

[0009] S3. Place the carbon fiber on a collecting plate in advance, and use melt direct writing technology to evenly spray the spinning onto the carbon fiber to prepare the functional fiber mesh material.

[0010] Furthermore, the functional fiber mesh material for adsorbing aquatic antibiotics is prepared by melt direct writing technology, and ferroferric oxide, activated carbon and polymer powder are physically blended in a mass ratio of 1:1 to 2:1-10, and then shaken and added into a feed barrel.

[0011] Preferably, the activated carbon is powdered activated carbon.

[0012] Preferably, the polymer in step S1 is one or more of polycaprolactone (PCL), polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), ethylene-vinyl acetate (EVA), polyethylene terephthalate (PET), and polyether sulfone (PES).

[0013] When two of the following are used, they are mixed in a ratio of 1:1 to 10: When three of the following are used, they are mixed in a ratio of 1:1 to 10:1 to 10. Preferably, the nozzle temperature in step S2 is 80-300°C (the nozzle temperature is determined according to the melting point of the selected polymer, which can be higher than the melting point and lower than 300°C), the nozzle loading voltage is 2.5-3.5KV, the distance from the nozzle to the collecting plate is 1-6mm, and the movement speed of the collecting plate is 30-36mm·s -1 , the inner diameter of the nozzle is 0.2-0.5mm.

[0014] Preferably, the fiber diameter is 1-20 um, and the porosity of the mesh material is 80-90%.

[0015] In the above steps, S1 mixes ferroferric oxide, activated carbon and selected polymer powder thoroughly and evenly and then adds the mixture into the feed barrel as direct writing raw materials, so that the catalytic particles and activated carbon powder are evenly dispersed in the polymer to ensure the stable progress of the subsequent adsorption reaction.

[0016] When S2 uses melt direct writing technology, the blend in the feed barrel is heated and melted into a molten state at high temperature. There is no need to add additional solvents, and there is no environmental burden or impact on the mixture. The air pressure generated by the air pump is used as a power source to extrude the molten mixture from the spinning nozzle, which is simple and feasible.

[0017] S3 places the carbon fiber on a collecting plate, repeatedly writes the molten mixture on the carbon fiber, and naturally dries to prepare a micro-nano bundle fiber composite material.

[0018] The present invention also provides a functional fiber mesh material prepared by the above preparation method.

[0019] The present invention also provides a method for removing antibiotics from water, wherein the method uses the functional fiber mesh material as an adsorption material.

[0020] The present invention also provides application of the functional fiber mesh material in the field of water treatment.

[0021] The beneficial technical effects of the present invention are:

[0022] 1. The functional fiber mesh material based on carbon fiber melt direct writing for adsorbing antibiotics in water provided by the present invention can precisely control the functional fiber material by melt direct writing technology, and the obtained fibers have high uniformity and uniform size, with fiber diameters ranging from nanometers to tens of microns; the fibers are overlapped and cross-linked on the carbon fiber substrate to form a mesh structure, providing a strong specific surface area to obtain a larger adsorption capacity, which is conducive to achieving efficient antibiotic adsorption effects.

[0023] 2. The functional fiber mesh material provided by the present invention uses carbon fiber as a substrate. The carbon fiber has excellent mechanical properties, is resistant to acid and alkali corrosion, and has strong adaptability to water bodies, providing good physical and chemical advantages for the adsorption treatment of antibiotic wastewater.

[0024] 3. In the functional fiber mesh material based on carbon fiber melt direct writing for adsorbing antibiotics in water provided by the present invention, ferrosoferric oxide is confined in a stable mesh structure and evenly distributed, which is conducive to achieving efficient catalysis.

[0025] 4. The current limitation of water antibiotic adsorption technology lies in the recovery and regeneration of adsorbents. The existence form of traditional functional nanomaterials makes them another pollution burden for the water environment, and their inability to be recycled leads to low utilization rate, and their adsorption effect on antibiotics needs to be improved. The present invention uses carbon fiber as a substrate to support this functional material, and the macroscopic bundle shape makes it easy to recycle and better exert the adsorption effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the effect of the present invention on adsorbing antibiotics in water.

[0027] Figure 2 The adsorption removal rate of tetracycline by the network functional material prepared in Example 1 of the present invention at different pH values.

[0028] Figure 3 The adsorption effect of the network functional material prepared in Example 1 of the present invention on streptomycin, erythromycin and kanamycin.

[0029] Figure 4 The removal rate of tetracycline by the mesh functional material prepared in Example 1 of the present invention at different recycling times. DETAILED DESCRIPTION

[0030] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Embodiment 1:

[0032] The method for preparing a functional fiber mesh material for adsorbing antibiotics in water based on carbon fiber melt direct writing provided by the present invention is as follows:

[0033] Ferroferric oxide, activated carbon powder and polycaprolactone (PCL) powder were physically blended in a mass ratio of 1:1:5, and then shaken and added to the feed barrel. The nozzle temperature of the melt direct writing spinning machine was set to 80°C, and the blend in the feed barrel was heated and melted into a molten state at high temperature. The air pressure generated by the air pump was used as a power source to extrude the molten mixture from the spinning nozzle; the carbon fiber was placed on the collection plate in advance, the nozzle loading voltage was set to 2.5KV, and the collection plate movement speed was 30mm·s -1 The inner diameter of the nozzle is 0.2 mm, the distance from the nozzle to the collecting plate is 2 mm, and the functional fiber mesh material can be prepared by uniformly spraying the spinning onto the carbon fiber using the melt direct writing technology. It can be seen from the measurement that the fiber diameter is 5 to 10 um, and the porosity of the mesh material is 87%.

[0034] Embodiment 2:

[0035] The method for preparing a functional fiber mesh material for adsorbing antibiotics in water based on carbon fiber melt direct writing provided by the present invention is as follows:

[0036] Ferroferric oxide, activated carbon powder, polyethylene (PE) and polyethersulfone (PES) powder were physically blended in a mass ratio of 1:2:5:5, and then shaken and added to the feed barrel. The nozzle temperature of the melt direct spinning machine was set to 300°C, and the blend in the feed barrel was heated and melted into a molten state at high temperature. The air pressure generated by the air pump was used as a power source to extrude the molten mixture from the spinning nozzle; the carbon fiber was placed on the collection plate in advance, the nozzle loading voltage was set to 3KV, and the collection plate movement speed was 35mm·s -1 The inner diameter of the nozzle is 0.4 mm, the distance from the nozzle to the collecting plate is 5 mm, and the functional fiber mesh material can be prepared by uniformly spraying the spinning onto the carbon fiber using the melt direct writing technology. The fiber diameter is 5 to 10 um, and the porosity of the mesh material is 90%.

[0037] Application Example 1

[0038] 5 mg of the mesh functional material prepared in Examples 1 and 2 was added to 20 mL of tetracycline solution (concentration: 40 mg / L) to construct a 0.25 g / L system. An adsorption experiment was conducted in a 50 mL conical flask, and the pH was adjusted to 7 by dropping a small amount of sulfuric acid or sodium hydroxide, and a rotor was placed on a stirring table with a speed of 200 rpm, and the reaction was continued for 3 hours. It can be seen that the functional mesh material provided by the present invention can achieve efficient adsorption and removal of tetracycline within 2 hours, and the adsorption removal rate is more than 95%.

[0039] Application Example 2

[0040] According to the method of Application Example 1, a small amount of sulfuric acid or sodium hydroxide was added to adjust the pH to 2, 4, 6, 8, 10, and 12, respectively, and the mesh functional material prepared in Example 1 was used to adsorb and remove tetracycline. After adsorption for 2 hours, the removal rate of tetracycline was Figure 2 It can be seen that when the pH is 6-8, the tetracycline removal rate can be maintained at about 95%, and when the pH is extended to 2-12, the tetracycline removal rate can still be as high as more than 60%. It can be seen that the composite material prepared by the present invention has a relatively stable adsorption effect in acid and alkali solutions and can be used for adsorption in a variety of environments.

[0041] Application Example 3

[0042] The tetracycline in Application 1 was replaced by streptomycin, erythromycin and kanamycin respectively, and the adsorption effect of the composite material prepared in Example 1 was investigated. After 2 hours of adsorption, the removal rates of various antibiotics were shown in Table 1. Figure 3 It can be seen that after 2 hours of adsorption, the removal rates of streptomycin, erythromycin and kanamycin are 92.1%, 86.8% and 95.9% respectively, which means that the composite material prepared by the present invention can have a good adsorption effect on a variety of antibiotics.

[0043] Application Example 4

[0044] The adsorption regeneration experiment of the composite material of the present invention can use sodium hydroxide as a desorbent. The saturated material after adsorption (the composite material prepared in Example 1 in Application Example 1) is added to 0.1 mol / L (100 mL) NaOH and stirred at room temperature for 6 hours. Then, it is filtered by suction and the desorbed sample is collected by washing with pure water. Finally, the sample is dried in an oven at 70°C and reused in the next round of adsorption experiments. A total of 8 cyclic regeneration experiments were carried out. Figure 4 It can be seen that after 8 consecutive cycles, the reuse efficiency of the mesh functional material of the present invention is still very high, and the tetracycline removal rate is still above 80%, indicating that the functional material of the present invention has good reuse performance.

[0045] Comparative Example 1

[0046] The addition of activated carbon and ferrosoferric oxide in Example 1 was omitted, and the other steps and conditions were consistent with those in Example 1, thereby obtaining a mesh composite material free of ferrosoferric oxide and activated carbon.

[0047] The adsorption performance of the composite material prepared in Comparative Example 1 was investigated in the same manner as in Application Example 1. The results are shown in Figure 1 It can be seen that after degradation for 3 h, the adsorption performance of the composite material of Comparative Example 1 for tetracycline is very limited, and only a very small amount of tetracycline can be adsorbed.

[0048] Comparative Example 2

[0049] The addition of ferrosoferric oxide in Example 1 was omitted, and the other steps and conditions were consistent with those in Example 1, thereby obtaining a network composite material free of ferrosoferric oxide.

[0050] The adsorption performance of the composite material prepared in Comparative Example 2 was investigated in the same manner as in Application Example 1. The results are shown in Figure 1 It can be seen that when degraded for 3 hours, the composite material of Comparative Example 2 has a certain adsorption effect on tetracycline, but the tetracycline removal rate is only 72.5%.

[0051] Comparative Example 3

[0052] The addition of activated carbon in Example 1 was omitted, and the other steps and conditions were consistent with Example 1, thereby obtaining a mesh composite material without activated carbon.

[0053] The adsorption performance of the composite material prepared in Comparative Example 3 was investigated in the same manner as in Application Example 1. The results are shown in Figure 1 It can be seen that when degraded for 3h, the composite material of Comparative Example 3 has a certain adsorption effect on tetracycline, but the tetracycline removal rate is only 67.2%.

[0054] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a functional fiber mesh material based on carbon fiber melt direct writing to absorb antibiotics in water, characterized in that: The following steps are involved: S1. Physically blend ferroferric oxide, activated carbon and polymer powder as direct writing raw materials, shake well and add them into the feed barrel; S2, heating the blend in the feed barrel at high temperature to melt it into a molten state, and using the air pressure generated by the air pump as a power source to extrude the molten mixture from the spinning nozzle; S3, placing the carbon fiber on a collecting plate in advance, and using melt direct writing technology to evenly spray the spinning onto the carbon fiber, so as to prepare the functional fiber mesh material; Wherein, the ferroferric oxide, activated carbon and polymer powder are physically blended in a mass ratio of 1:1-2:1-10; The polymer in step S1 is one or more of polycaprolactone, polyethylene, polypropylene, polystyrene, polyvinyl chloride, ethylene-vinyl acetate, polyethylene terephthalate, and polyether sulfone; In the functional fiber mesh material, the fiber diameter is 1-20um, and the porosity of the mesh material is 80-90%.

2. The preparation method according to claim 1, characterized in that: When two of the polycaprolactone, polyethylene, polypropylene, polystyrene, polyvinyl chloride, ethylene-vinyl acetate, polyethylene terephthalate, and polyether sulfone are used, they are mixed in a mass ratio of 1:1 to 10.

3. The preparation method according to claim 1 or 2, characterized in that: The nozzle temperature in step S2 is 80-300° C., and the nozzle loading voltage is 2.5-3.5 KV.

4. The preparation method according to claim 3, characterized in that: The distance from the nozzle to the collecting plate in step S2 is 1-6 mm, and the moving speed of the collecting plate is 30-36 mm·s -1 , the inner diameter of the nozzle is 0.2-0.5 mm.

5. The functional fiber mesh material prepared according to the preparation method according to any one of claims 1 to 4.

6. A method for removing antibiotics from water, characterized in that: The method uses the functional fiber mesh material according to claim 5 as the adsorption material.

7. Use of the functional fiber mesh material according to claim 5 in the field of adsorbing antibiotics in water.

Citation Information

Patent Citations

  • Preparation method for magnetic active carbon fibers

    CN104047071A

  • Magnetic powdered activated carbon adsorbent and preparation method and application thereof

    CN106475066A